Development of 3D Printed Autonomous Warehouse Robot Using Mecanum Wheel and Robot Arm - Hadisujoto, Budi; Rabbani, Ariq Naufal; Saptaji, Kushendarsyah; Fernandez, Nikolas Krisma; Wibowo, Djati (Journal of Applied Sciences and Advanced Technology, 2023)
Industrial revolution 4.0 has affected many industries, including warehouse management. Warehouse management so far has progressed with the introduction of automation, i.e. using warehouse robots to improve the flow of the warehouse management. This work discusses and builds a 3D-printed warehouse robot prototype in the form of mobile manipulator with mecanum wheel. The mecanum wheel is chosen for better kinematics movement. The prototype warehouse robot is designed to accept command wirelessly through Bluetooth via an Android application. The prototype robot was successfully built and tested. The movement test shows it can move freely in any direction due to the mecanum wheel. However, the robot still has poor repeatability and reliability. Based on the result, the prototype can serve as a basis for an affordable warehouse robot, and the future work to improve the repeatability and reliability of the robot is strongly encouraged.